Quality of Newborn Care and Associated Factors: An analysis of the 2022 Kenya Demographic and Health Survey - Asiimwe, John Baptist; Amwiine, Earnest; Namulema, Angella; Sserwanja, Quraish; Namatovu, Imelda; Nuwabaine, Lilian (PLOS Global Public Health, 2024)
Kenya one of the African countries has pledged to reduce neonatal death as per the 2030 World Health Organization target. Providing high-quality newborn care is critical in minimizing neonatal mortality. This study aimed to determine the factors that influence the quality of newborn care in Kenya. Secondary data from 11,863 participants of the 2022 Kenya Demographic and Health Survey (KDHS) were analyzed. The participants were chosen using two-stage stratified sampling. The quality of newborn care was operationalized as receiving all components of newborn care after childbirth, as reported by the mother. Using SPSS (version 29), univariate and multivariable logistic regression analyses were used to analyse the data. In this study, 32.7% (95% confidence interval [CI]: 31.0%-34.5%) of the mothers reported that their newborns had received all components of quality neonatal care after childbirth. Mothers who spent an average of one hour accessing the health facilities compared with those who spent less than half an hour were 1.33 (95%CI: 1.01–1.75) times more likely to report that their newborns had received quality newborn care. Mothers who gave birth in a non-government organization health facility were 30.37 (95%CI: 2.69–343.20) times more likely to report that their newborns had received quality newborn care compared with those who delivered from a faith-based organization. On the contrary, in terms of regions, mothers who lived in Nyanza, Eastern, and Rift Valley provinces compared with those who lived in the coastal regions were 0.53 (95%CI: 0.34–0.82), 0.61 (95%CI: 0.39–0.94), and 0.62 (95%CI: 0.41–0.93) times less likely to report that their newborns had received quality newborn care, respectively. Mothers who subscribed to other religions or faith (0.28 (95%CI: 0.10–0.76) compared with those from the Christian faith, were less likely to report that their newborns had received quality newborn care. Finally, mothers who gave birth through cesarean section were 0.44 (95%CI: 0.32–0.61) times less likely to report that their newborns had received quality newborn care than mothers who gave birth through spontaneous vaginal delivery. The study indicates that about a third of the neonates received quality newborn care and that facility-related and parental social factors were associated with receiving quality newborn care. Stakeholders need to pay more attention to newborn babies whose mothers come from certain regions of Kenya where the quality of newborn care was found to be low, minority religious faith denominations, and those who delivered by ceasearen section. Stakeholders also should focus on strengthening collaborations with NGO health facilities and achieving universal health coverage to improve the quality of newborn care provided in health facilities.